Aerobic energy expenditure and intensity prediction during a specific circuit weight training: A pilot study - Peinado, P. J. B.; Sanchez, M. A.; Molina, V. D.; Lozano, A. B. P.; Montero, F. J. C. (Journal of Human Sport & Exercise, 2010)
During circuit weight training (CWT), workloads, index of intensity as well as estimation of energy expenditure (EE) have been under estimated. The aim of this study was to describe and evaluate physiological variables and gender related differences, including intensity prediction and EE, during CWT at different intensities. Twenty six subjects were assessed in a CWT, fourteen men and twelve women. The CWT program was performed at six different intensities, 40%, 50%, 60%, 70%, 80% and 85% of 15RM. Seven exercises made up the circuit: sitting bench press, leg press, lat pull down, shoulder press, hamstring curl, biceps curl, and triceps cable push downs. A polar heart rate monitor and a portable metabolic system were used to measure heart rate (HR), intensity measured relative to the HR reserve, cardiorespiratory variables, EE and EE relative to muscle mass (EEMM). Differences between genders were observed at the following variables: HR, intensity measured relative to the HR reserve (in percentage), VO2, VCO2, VE, RER, aerobic EE and EEMM. The EE was significantly higher in men during the six intensities, but differences did not exist for EEMM from 70% to 85%. In addition HR, load and body weight were used to predict intensity and two gender specific equations were obtained for men and women [I (%) = 57.265 + 0.512HR - 0.696HRmax + 1.035 Loadavg + 0.188 Body Weight (R2=0.92; SEE=4.9%) for men; I (%) = 4.036 + 0.412HR% + 1.667 Loadavg (R2=0.79; SEE=7.7%) for women]. Thus, we conclude that gender related differences are present during CWT for EE, even when expressed relative to muscle mass, in addition HR, work load and body weight can estimate the intensity during CWT.